Bank Loan, Inflation, and Farmers Welfare: Data Analysis by Province in Indonesia - Wibowo, Buddi (Asian Development Policy Review, 2019)
The effects of bank loans and access to formal financial institutions on rural economic growth and farmers’ welfare in all provinces in Indonesia have not been previously comprehensively documented with accurate, scientific methodology. This study examines the relationship of bank loans to the Farmers’ Terms of Trade and also provides a comprehensive analysis on some control variables such as inflation and agricultural sector productivity. The results show that bank loans do not significantly affect the welfare of farmers. Inflation and farmers’ welfare have an inverted U shape pattern and relationship which indicates that while low inflation rates are positively related to farmer’s welfare; higher inflation rates will drastically decrease the level of welfare. The productivity of the agricultural sector affects the welfare of farmers but must be carefully interpreted in the context of the Indonesian economy’s condition which is currently undergoing an economic transformation